Typification of Hammada articulata (Amaranthaceae) - Ferrer-Gallego, P. Pablo; Crespo, Manuel B. (Phytotaxa, 2020)
The name Caroxylon articulatum, basionym of Hammada articulata, and based on the illegitimate name “Salsola articula Cav.” is typified from a specimen collected by A.J. Cavanilles in Elda (Alicante, Spain) in 1791.